SANCTIONS IMPLEMENTATION ON CHILD AS CRIMINAL ON RESTORATIVE JUSTICE PERSPECTIVE (POLRES MATARAM JURISDICTION) - ,SH, Fahrurrozi (Jurnal IUS, 2015)
This research aims are to analyze the implementation of sanction on children as criminal in restorative justice perspective. Legal issues that arise on this research are, how is the sanction implementation on children as a criminal on restorative justice perspective in Polres Mataram Jurisdiction and how the effectivity of sanction implementation on children as criminal on restorative justice perspective in Polres Mataram Jurisdiction.Â This research is normative-empirical legal research beside the use of statute this research also use the data on the field related to the issues on this research. Can be concluded that the sanction implementation against children as criminal on restorative justice perspective in Polres Mataram Jurisdiction is be returned according to articleÂ 11 and 71 paragraph (1) letter b number 3 Law Number 11 Year 2012. And the effectiveness on sanctions implementation against children on restorative justice perspective in Polres Mataram Jurisdiction is quite effective because of victim, criminal and society feel satisfied with the restorative justice settlement. Kay Word : Sanctions, Children, Restorative Justice.